2003
DOI: 10.4049/jimmunol.171.1.426
|View full text |Cite
|
Sign up to set email alerts
|

Bcl6 Is a Transcriptional Repressor for theIL-18Gene

Abstract: Bcl6 functions as a sequence-specific transcriptional repressor, and Bcl6-deficient (Bcl6−/−) mice have been reported to display Th2-type inflammatory diseases in multiple organs. Since IL-18 is a potent stimulator of Th2 cells, we examined the expression of IL-18 mRNA in bone marrow-derived macrophages from Bcl6−/− mice after LPS stimulation. Here we show that the expression was strikingly up-regulated after stimulation. The expression was also up-regulated in RAW264 cells, a murine macrophage cell line, by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 51 publications
2
35
1
Order By: Relevance
“…The Bcl-6 response element in intron 5 (BRE1) is conserved in the human gene and was shown to be bound by Bcl-6 both in vitro and in vivo. Our study adds prdm1 to the list of IL-5, IL-18, B7-1, and Bcl-6 itself that are direct targets of Bcl-6 (22)(23)(24)(25)(26). Our results are consistent with previous microarray studies which identified PRDM1 as a direct target of Bcl-6 repression (5).…”
Section: The Mouse Prdm1 Gene Is a Direct Target Of Bcl-6-mediated Trsupporting
confidence: 82%
“…The Bcl-6 response element in intron 5 (BRE1) is conserved in the human gene and was shown to be bound by Bcl-6 both in vitro and in vivo. Our study adds prdm1 to the list of IL-5, IL-18, B7-1, and Bcl-6 itself that are direct targets of Bcl-6 (22)(23)(24)(25)(26). Our results are consistent with previous microarray studies which identified PRDM1 as a direct target of Bcl-6 repression (5).…”
Section: The Mouse Prdm1 Gene Is a Direct Target Of Bcl-6-mediated Trsupporting
confidence: 82%
“…As is shown in Figure 1E, prominent upregulation of promoter activity was observed upon the transfection of the P179 construct. The IL-18 promoter harbors several positive elements, including AP-1, NF-B, and ICSBP (Kim et al, 2000), and negative elements including bcl-6 (Takeda et al, 2003). Bcl-6, which is a transcriptional repressor for IL-18 gene expression via the binding of Ϫ2574 to Ϫ2565 bp of the IL-18 P1 promoter, was also increased under hypoxic conditions.…”
Section: Il-18 Gene Expression Is Induced Under Hypoxic Conditionsmentioning
confidence: 97%
“…We used BCL6 mRNA and protein expression, and mutation and translocation data, to perform supervised analyses of the expression of BCL6 target genes 31,39,40 in the different subgroups of DLBCL. Target gene selection was described in the Materials and methods section and repression of the majority of the target genes was observed in all three subsets when the level of BCL6 expression was sufficiently high at both protein or mRNA level.…”
Section: Association Of Bcl6 Gene Abnormalities and Bcl6 Target Gene mentioning
confidence: 99%